Cytotoxic and Antimicrobial Evaluations of Novel Apoptotic and Anti‐Angiogenic Spiro Cyclic 2‐Oxindole Derivatives of 2‐Amino‐tetrahydroquinolin‐5‐one. Issue 2 (February 2015) - Ghozlan, Said A. S.; Mohamed, Magda F.; Ahmed, Ahmed G.; Shouman, Samia A.; Attia, Yasmin M.; Abdelhamid, Ismail A.
<x xml:space="preserve">Abstract</x> A novel series of cyclic 2‐oxindole derivatives incorporating 2‐amino‐tetrahydroquinolin‐5‐one were prepared. The structures of the prepared compounds were elucidated using different spectral tools. The regio‐orientation of the reaction products was elucidated through NOE difference experiments and through using substituents on the ortho position to affect further cyclization. Antitumor and antimicrobial evaluations were performed on the prepared compounds. Most of these compounds exhibited high to moderate antimicrobial activity. With respect to the antitumor activity, the compounds showed more potent cytotoxic effect only toward the human breast cancer cell line MCF‐7. Also, we found that derivatives containing an ester group (8c, 11b, 14b, and 15b) are more active than those containing a cyanide group (8a, 11a, 14a, and 15a). Moreover, compounds 15b and 8b are the most active derivatives in this group. These two compounds showed apoptotic inhibition of the proliferation of human breast adenocarcinoma MCF‐7 cells through DNA fragmentation, induction of the tumor suppressor protein p53, induction of caspase‐9, and finally the inhibition of angiogenesis by decreasing vascular endothelial growth factor expression and secretion.